A Comprehensive Approach to Pouch Disorders. Issue 3 (16th August 2018) - Quinn, Kevin P; Lightner, Amy L; Faubion, William A; Raffals, Laura E
Abstract: Restorative proctocolectomy with ileal pouch-anal anastomosis (IPAA) is the surgical procedure of choice for patients with medically refractory ulcerative colitis (UC) or indeterminate colitis, UC with colonic dysplasia or neoplasia, and familial adenomatous polyposis. In general, patients experience good function outcomes and quality of life with an IPAA. Although pouchitis is the most well-recognized and frequent complication after IPAA, a number of additional inflammatory, postsurgical, structural, neoplastic, and functional complications may occur, resulting in pouch dysfunction. We herein provide a comprehensive review of pouch function and an approach to diagnosis and management of pouch complications.